Fikih maṣlaḥah atas Perubahan Fungsi Lahan: Dari Pertanian Menjadi Kawasan Wisata di Kab. Wonosobo - Sari, Fatmah (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
This article discusses the conversion of agricultural land into a tourist area from the perspective of maslahah mursalah. The qualitative method and the type of research used is field research using an empirical legal approach. The results of the study of the conversion of agricultural land into a tourist attraction in Damarkasiyan Village, which was started in 2015 by local youth, have had a positive economic impact: increased employment, community income, and diversifica-tion of income sources, along with the high value of land rent in the non-agricultural sector. The benefits obtained by the community as a whole are greater, so that this land conversion can be considered in accordance with the principle of maslahah mursalah, which emphasizes universal benefits.